VLI Leadership Institute An Information System Study - Alejandro, Cherrie May; Ang, Sheila; Pon-an, Elsie; Salva, Claire (College of Engineering, 1999)
Victory Leadership Institute (VLI) is the leadership school of Victory Christian Fellowship. VLI was established to help fulfill their part in the Great Commission. Jesus commanded the Church to go and make disciples of all nations, and to take the Gospel to the ends of the earth. VLI believes that the most effective way to accomplish this is through the church planting and world missions. VLU aims to train, equip, and launch hundreds of young men and women as church planters and lay leaders into the nations and in society. VLI is uniquely tailored to the Victory vision. Its curriculum is designed to teach, impart, and implement the mission and vision as a movement. As a result, the effectivity and efficiency as a church will increase. VLI is preparing for the future by training and launching a new generation of leaders. A great harvest is coming and there is a need to train and raise up leaders to contain it. VLI is Victory's commitment to the future. They are in this for the long haul and strongly expect results. Victory Leadership Institute began in June of 1993 with a hundred and eighty students enrolled. Since then, many more students have discovered their calling and purpose in lives and have been equipped for ministry through the help of VLI. VLI's approach to teaching is from a local church context. The programs are designed to be practical and readily applicable in the local church. Most of the illustrations, problems, and cases that will be used are from actual pastoring and church planting experience. The interaction and dynamics of the school is such that it is an extension of the local church. VLI's motto is Making Disciples, Training Leaders, and Planting Churches. That is what VLI seeks to accomplish in each class of VLI. BLI believes that God has called us to make disciples and followers of Jesus, not just converts. It will be these disciples who, when trained and equipped, will take the Gospel into the ends of the earth and advance His Kingdom by planting churches. VLI has four emphases: LEADERSHIP. VLI believes that one of the most effective ways to reforms society and to disciple the nations is to reach the leaders of tomorrow. Leaders who will take the Gospel and apply Biblical principles in the arts, education, media, family life, political systems, law, business, church, the sciences, economics, in all of society. The leaders are the ones who influence the shape, fabric, and direction of society. Leaders armed with Christian convictions are the most needed in the corridors of power and influence today. LOCAL CHURCH. VLI believes and is committed to the role and place of the local church in the Kingdom of God. Every new believer must be added to and every disciple must function in a local church in order for them to grow. A person's destiny is tied with a local church's calling. It is in the context of the local church that Christians are trained and released to do the works of the ministry. CHRUCH PLANTING AND WORLD MISSSIONS. Victory was birthed through missions and continues o grow through missions. VLI believes that the most effective way to fulfill the Great Commission is through church planting and world missions. God has called each Christian to be a witness and to make an impact to the ends of the earth. Mission is a nonnegotiable priority in Victory. To honor God and advance His Kingdom by making disciples, training leaders, and planting churches in the Philippines, Asia, and the world. Victory Leadership Institute (VLI) is the leadership school of Victory Christian Fellowship whose mission is to provide in-depth training for: *Church Planters - long and short-term missionaries *Pastors - current and future pastors *Future Ministries - those who sense a specific call and direction in their lives and desire further equipping, training, and preparation to fulfill the call. *Lay Leaders - tentmakers, cell leaders, ministry heads, etc.